Costs and Impacts of Utilizing National Health Insurance Reducing the Economic Burden of Hypertension Patients - Adila Solida; Dwi Noerjoedianto; Arnild Augina Mekarisce; Andi Subandi (Universitas Aisyah Pringsewu, 2023)
The prevalence of hypertension ranks as the highest incidence of disease in Jambi Province in the last 5 years. The cost of treatment and management of hypertension that must be borne by the community is relatively high. The existence of a cost reduction from the National Health Insurance (JKN) program is expected to reduce the economic burden caused. This study aims to analyze the difference in the average costs due to hypertension between patients who use JKN and patients who pay out of pocket in Jambi City. A Study based on economic evaluation with a quantitative approach, was conducted in Jambi City in 2022. There were 165 respondents selected by purposive sampling technique. The study instrument was in the form of a questionnaire. Data processing using statistical software with descriptive statistical analysis stage and bivariate T-test analysis. The results of the study showed that there were differences in the average direct medical costs (p = 0.000), direct non-medical costs (p = 0.034), and the total costs due to hypertension (p = 0.018) between patients who used JKN and patients who pay out of pocket. The conclusion of the study is that the difference in the average costs incurred by hypertension sufferers who utilize JKN has an impact on reducing the family's economic burden, especially in the direct medical cost component. Abstrak: Prevalensi hipertensi menempati urutan teratas sebagai kejadian penyakit paling banyak di Provinsi Jambi dalam 5 tahun terakhir. Biaya pengobatan dan penanganan hipertensi yang harus ditanggung masyarakat relatif tinggi. Adanya penekanan biaya dari program Jaminan Kesehatan Nasional (JKN) diharapkan mengurangi beban ekonomi yang ditimbulkan. Studi ini bertujuan menganalisis perbedaan rerata biaya akibat penyakit hipertensi antara penderita yang memanfaatkan JKN dengan penderita yang mengeluarkan biaya dari kantong sendiri di Kota Jambi. Studi berbasis evaluasi ekonomi dengan pendekatan kuantitatif, dilakukan di Kota Jambi tahun 2022. Responden berjumlah 165 orang yang dipilih dengan teknik purposive sampling. Instrumen studi berupa angket. Pengolahan data menggunakan software statistik dengan tahap analisis statistik deskriptif dan analisis bivariat uji-T. Hasil studi bahwa terdapat perbedaan rerata biaya langsung medis (p=0,000), biaya langsung non medis (p=0,034), dan total biaya akibat penyakit hipertensi (p=0,018) antara penderita yang memanfaatkan JKN dengan penderita yang mengeluarkan biaya dari kantong sendiri. Kesimpulan studi bahwa perbedaan rerata biaya yang dikeluarkan penderita hipertensi yang memanfaatkan JKN berdampak pada penurunan beban ekonomi keluarga terutama pada komponen biaya langsung medis.